Prevalence and molecular characterization of Beta-lactamase resistance gene in multidrug resistance bacteria, Proteus spp. - S. Salih, Sabiha; J. Mohammed, Shno; M Noori, Imad; MA Mohammed, Lana; A. Hama Soor, Taib (Kurdistan Journal of Applied Research, 2019)
Existing of drug resistance bacteria in meat is a series of health concern and beta-lactamase is responsible to generate multi drug resistances in bacteria. Meat is a source of delivering food born pathogen bacteria including Proteus species. Recently Proteus bacteria developed drug resistance against many antimicrobial drugs and it causes difficulty in patient’s treatment. Hence its important to indicate the rate of Proteus species, P. mirabilis and P. Vulgaris, in the meat of different animals and to find the prevalence of b-lactamase resistance genes (blaTEM-1, blaCMY, blaCMY2, blaShv, blaOXA, and blaCTX) in Proteus species. Molecular identification of Proteus bacteria was confirmed by PCR amplification of part of 16S rRNA using Proteus specific set of primers. 70 meat samples (cattle, sheep, chicken, turkey, goat, and fish) were collected in local meat shops in the center of Sulaimani city. 29 (41.4%) samples were positive to Proteus species and 22 (75.87%) isolates were P. mirabilis and seven (24.13%) were P. vulgaris based on conventional biochemical tests. The drug sensitivity test was performed for all isolates using a disk diffusion assay (Kirby Bauer test). The multidrug resistance was found in all isolates and the most common drug resistance phenotype were against tetracycline, rifampin, and doxycycline, while the imepenem, tobramycin, and meropenem remain more effective against the bacteria. Resistance genes, blaTEM-1, and blaShv were found in five isolates (17.2%) of Proteus. Three isolates (10.3%) were positive to blaTEM-1 resistance gene and two isolates (6.8%) were positive to blaShv. All resistance genes recorded in this study were recovered in P. mirabilis and none of them was reported in p. vulgaris. None of the isolates was positive to beta-lactamase genes, blaCMY, blaCMY2, blaOXA, and blaCTX.